A qualitative exploration of challenges in childhood TB patients identification and diagnosis in Bangladesh - Shitol, Sharmin Akter; Saha, Avijit; Barua, Mrittika; Towhid, Kazi Md Saleheen; Islam, Akramul; Sarker, Malabika (Heliyon, 2023)
Background - As childhood tuberculosis is difficult to identify and diagnose, the experiences of the caregivers and healthcare providers of childhood tuberculosis patients remain a potential area of study. This study aims to illustrate the challenges caregivers and healthcare providers encounter in identifying and diagnosing childhood tuberculosis in two sub-districts of Bangladesh. - Methods - We conducted semi-structured in-depth interviews with eight caregivers of childhood tuberculosis patients and key informant interviews with 36 healthcare providers from September 2020 to December 2020 from different levels of the tuberculosis control program in Keraniganj (with high childhood tuberculosis cases notification), Faridpur Sadar (with low childhood tuberculosis cases notification), and Dhaka city. - Results - There is a dearth of understanding among caregivers about childhood tuberculosis. Passive case finding process and focus on cough during community mobilisation contribute to the delay in childhood tuberculosis identification. The stigmatisation that caregivers anticipate and experience has an impact on their mental health and implies that there are misunderstandings about tuberculosis in the community. Furthermore, diagnostic dilemma among healthcare providers accounts for diagnosis delays. Some, but not all, institutions in different geographical locations provide free diagnostic tests and have GeneXpert devices. - Conclusions - Various factors, including caregivers' knowledge and experience, the process of case finding and community mobilization, healthcare providers' way of service provision and diagnosis, and the unavailability of required logistics at facilities challenge the identification and diagnosis of childhood tuberculosis that need to be minimized for childhood tuberculosis's early identification, diagnosis, treatment initiation, and successful completion of treatment. Awareness should also be raised in the community of childhood tuberculosis.